Community Structure of Fiddler Crabs (Uca) in the Mangrove Ecosystem of Lalombi Village, South Banawa District, Donggala Regency - Berlinda Austin Paliwan; Bustamin; Abd. Rauf; Syech Zainal; Moh Sabran; Raya Agni (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the community structure of fiddler crabs (Uca) in the mangrove ecosystem of Lalombi Village, South Banawa District, Donggala Regency, and to utilize the research findings as instructional media in the form of a flipbook. This ecological study employed a quantitative descriptive approach based on community structure analysis, with samples collected using purposive sampling. The parameters analyzed included species composition, density, the Shannon–Wiener diversity index, the Simpson dominance index, and the evenness index, along with environmental variables such as temperature, salinity, pH, and substrate type. The results showed that the fiddler crab community in the mangrove ecosystem of Lalombi Village consisted of five species, namely Uca annulipes, Uca lactea, Uca forcipata, Uca tetragonon, and Uca dussumieri. Abundance varied across sampling stations, and the overall diversity level was classified as low to moderate. The occurrence frequency of these five fiddler crab species was very low. The recorded densities were 6 ind/m² for Uca annulipes, 3 ind/m² for Uca lactea, 5 ind/m² for Uca forcipata, 7 ind/m² for Uca tetragonon, and 3 ind/m² for Uca dussumieri, with a low dominance index. The environmental physicochemical conditions recorded for fiddler crab habitat were a temperature of 30°C, water pH of 8.25, salinity of 31, and a muddy substrate type. Overall, the fiddler crab community structure in the mangrove ecosystem of Lalombi Village was relatively stable, characterized by low to moderate diversity, low dominance, and a clumped distribution pattern influenced by substrate conditions and mangrove density.